2008
DOI: 10.1080/13625180701617589
|View full text |Cite
|
Sign up to set email alerts
|

Do contraceptive choices of Turkish married adolescents differ from those of older women?

Abstract: The distribution of contraceptive methods used was similar among the three age groups, but the absence of contraception was most frequent in the adolescent group. The adolescents we assessed, being married and having delivered at least once, are a highly selected group and not representative of adolescents in general. Nevertheless, their contraceptive choices did not differ from those of older women. The incidence of TOPs among them was quite high. Minimization of the frequent neglect of application of contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…Women older than 20 years (58%) more likely to choose traditional methods of contraception. 15 In our study, no differences in the application of CI in women of different ages, as in the study Dilbaza et al 30 In terms of preventive gynecological practice, middleaged respondents rarely go to gynecological control, Pap tests and breast self-examination more likely to work once a month. Younger respondents more likely to work the control gynecological examinations, the interval between Pap test is shorter, and rarely do breast self-examination of women of age medium.…”
Section: Discussionsupporting
confidence: 62%
“…Women older than 20 years (58%) more likely to choose traditional methods of contraception. 15 In our study, no differences in the application of CI in women of different ages, as in the study Dilbaza et al 30 In terms of preventive gynecological practice, middleaged respondents rarely go to gynecological control, Pap tests and breast self-examination more likely to work once a month. Younger respondents more likely to work the control gynecological examinations, the interval between Pap test is shorter, and rarely do breast self-examination of women of age medium.…”
Section: Discussionsupporting
confidence: 62%
“…Included studies often reported additional indicators, including fertility desires, defined as the percentage of women who wish to become pregnant in the next two years, to delay pregnancy by two or more years, or to have no more pregnancies (Dilbaz et al, 2008;Worku et al, 2015), and percentage of adolescents who felt pressure to become pregnant soon after marrying (Jejeebhoy et al, 2014). Almost half of the studies (n = 8) reported on contraceptive method mix, and the majority (n = 13) conducted additional analyses of factors associated with demand for contraception.…”
Section: Additional Reported Indicatorsmentioning
confidence: 99%
“…Asking adolescents about sex, fertility and use of contraception can be challenging, particularly in cultures where such topics are taboo. Only two studies (Iyoke et al, 2014;Jemmott et al, 2007) administered anonymous surveys and two collected data from medical records (Dilbaz et al, 2008;Meuwissen et al, 2006); the rest were conducted via face-to-face interviews. Only one of the reviewed studies mentioned that researchers were specially trained to conduct research with adolescents (Zavier & Jejeebhoy, 2012).…”
Section: Appropriate Modes Of Data Collection For Adolescent Populationsmentioning
confidence: 99%
“…Ankara merkezde Dilbaz ve arkadaşlarının yaptığı aile planlaması yöntem tercihlerini gösteren çalışmada yaş grupları arasında fark saptanmayıp, adolesan grupta doğum kontrol yöntemlerinin pek tercih edilmediği görülmüştür. [14] Sırbistan'daki çalışmada da tüm yaş gruplarındaki kadınların en sık geleneksel yöntemleri tercih ettikleri, 20-29 yaş grubunun kondom ve geri çekme yöntemi tercihlerinin daha yüksek olduğu saptanmıştır. [10]…”
Section: Yaşın Etkisiunclassified